Bringing Bottom of the Pyramid Markets and Consumers into the Economic Mainstream - Hammond, Al (Institutional Knowledge at Singapore Management University, 2012)
Governments and markets have failed to adequately serve the four billion consumers at the bottom of the economic pyramid (BOP). Al Hammond explains why this is so and outlines strategies for how different players can harness the growth of the BOP market.